Malignant melanoma: epidemiology, pathogenesis, diagnostics and innovative therapeutic methods - Magdalena Janus; Zuzanna Rzepka; Paulina Kaleta; Dorota Małgorzata Wrześniok (Polish Pharmaceutical Society, 2023)
Melanoma is the most common cause of death among people with skin cancer, and its development is most often associated with excessive exposure to ultraviolet radiation and predisposing genetic factors. Early detection of melanoma significantly reduces mortality in both the short and long term. Unfortunately, this cancer has the ability to quickly reach the malignant phase and metastasize to other organs. The typical treatment for melanoma is surgical resection, but over the last few years significant progress has also been made in the field of systemic therapies, which has led to a noticeable improvement in survival in patients with metastases. The article summarizes information about modern therapeutic methods used in patients with melanoma. Drugs belonging to BRAF kinase inhibitors: vemurafenib and dabrafenib are currently the first-line therapy for advanced melanomas with a confirmed BRAF gene mutation. Modern therapeutic strategies that have revolutionized the treatment of melanoma also include immunotherapy. By blocking inhibitory checkpoints of the immune system, it is possible to generate an anti-cancer response alone or in synergy with other types of therapy. These drugs target molecules that are pathologically overexpressed in melanoma, such as PD-1 or CTLA-4. Intralesional agents, such as oncolytic viruses, can also induce immune stimulation to destroy cancer cells. The only drug of this type registered so far for the treatment of melanoma is talimogene laherparepvec, which uses a genetically modified herpes simplex virus type 1. The possibility of individually tailored treatment to the patient is created by CAR-T therapy, which involves collecting tumor-infiltrating T lymphocytes from the patient, modifying them to obtain a receptor that specifically recognizes melanoma cells, and then multiply and introduce it into the patient's body. Recent findings have shown higher success rates with combinations of immunotherapy and chemotherapy, radiotherapy, or targeted molecular therapy. Despite the success of modern systemic therapy, many melanoma patients do not respond to treatment or develop drug resistance, which leads to the constant need to look for new solutions in the fight against this cancer.